Analysing Reading Comprehension of Primary School Students through Parenting Context - Inharjanto, Anselmus; Lisnani, Lisnani (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2023)
The unsatisfactory results of the Programme for International Student Assessment (PISA) in Indonesia related to reading become the urge for analysing students' reading comprehension. The objective of this research was to analyse the reading comprehension of Grade IV students at one of the private primary schools in Palembang by using a parenting context. The parenting context was implemented in the form of colouring picture stories. Further, this research employed descriptive qualitative method. Data collection techniques used were tests, questionnaires, and documentation. As regards sampling technique, a purposive sampling was applied, based on the class criteria of Grade IV students who enrolled the offline class. It should be noted that this study was conducted after the peak of pandemic crisis but most schools still enrolled online class. Finally, the results of this study demonstrate that students perceive they are most likely to learn and be motivated in learning English through colouring parenting-related pictures.